The The Use of Peer-Correction to Improve Student Writing Skill at STMIK Stikom Indonesia - Komang Trisnadewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
In the process of producing a writing in English, students certainly experiencedifficulties since English is a foreign language as experienced by students of STMIKSTIKOM Indonesia. The preliminary observation showed that students have problem inall components of writing and tends to repeat the same mistakes. To overcome theseproblems, peer-correction techniques are implemented. This study was conducted toimprove students’ writing skill using peer-correction, find the most affected component ofwriting and show students’ responses. There are three steps in this study includingpretest, implementation of peer-correction and post-test. Pre-test was conducted at thebeggining of the meeting with the aim of knowing the initial ability of students’ writing.The implementation of peer-correction was conducted in two cycles which each cycleincluding planning, implementation of action, observation and final reflection. Post testwas conducted in each cycle to determine the ability of students’ writing afterimplementing peer-correction techniques. The result showed that the implementation ofpeer-correction techniques was able to improve students’ writing skill in terms of content,organization, vocabulary, language and mechanics in which content is the most affected.Moreover, students showed positive response toward the implementation of peercorrection.